Dinamic of indicators of variation rhythmopulsometry and calcium-magnesium balance in the operating stress in patients with syrgery in the maxillofacial region - Vasiliy Vladimirovich Fisher; Ivan Victorovich Yatsuk; Vladimir Alexandrovich Baturin (Наука. Инновации. Технологии)
The purpose of this work is to study conjugate fluctuation parameter variation pulsometry with fluctuations in intracellular calcium and magnesium for men and women in different periods of operational stress. The stress intensity of the organism was assessed by the parameters of heart rate variability and the determination of the content of calcium and magnesium ions in erythrocytes before surgery, during surgery, on the third and fifth days after the operation. During the operative intervention, there was an explicable predominance of sympathetic regulation of the heart rhythm with normalization of indicators in the postoperative period and restoration of the normotonia state in the body. Electrolyte changes were manifested in the increase in the concentration of calcium ions in the postoperative period and in the decrease in the magnesium content in the cell by the ifth day of observation. Thus, despite normalization, changes in the calcium-magnesium balance were maintained for the ifth day after the operation, and for indicators of variation rhythmopulsometry.